Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1080/00984100050201640
|View full text |Cite
|
Sign up to set email alerts
|

Chrysotile Asbestos Fibers Detected in the Newborn Pups Following Gavage Feeding of Pregnant Mice

Abstract: Female pregnant mice were fed chrysotile asbestos suspension by gavage to determine whether there is transfer of fibers to the fetuses. Groups of mice were given 2 doses of either 50 microg chrysotile suspension in 0.2 ml sterile normal saline (treated), or 0.2 ml saline (control), and were allowed to mate 2 d later. After pregnancy was confirmed, the treated and control groups received 2 additional doses of chrysotile asbestos or saline on gestational d 7 and 12. Both groups were allowed to deliver naturally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…An experimental study demonstrated that, in mice, ingested asbestos fibres can cross the placenta and accumulate in the liver of the fetus. 35 This finding is in line with those from an epidemiological study that documented the presence of asbestos fibres in the liver of stillborn infants from mothers without a known occupational exposure to asbestos. 36 Due to the lack of information on established personal risk factors, we could not explore the role of asbestos in the initiation and/or promotion of CC.…”
Section: Discussionsupporting
confidence: 90%
“…An experimental study demonstrated that, in mice, ingested asbestos fibres can cross the placenta and accumulate in the liver of the fetus. 35 This finding is in line with those from an epidemiological study that documented the presence of asbestos fibres in the liver of stillborn infants from mothers without a known occupational exposure to asbestos. 36 Due to the lack of information on established personal risk factors, we could not explore the role of asbestos in the initiation and/or promotion of CC.…”
Section: Discussionsupporting
confidence: 90%
“…It is thus likely to speculate that intraperitoneally administered asbestos fibers in the present study might at least partly be carried by lymphatic or blood flow from peritoneal cavity. Some literature indicates that transplacental distribution of asbestos from dam to fetus (Cunnibgham and Pontecraft, 1974;Haque et al, 1992Haque et al, and 2001. So, asbestos fibers might penetrate past the placenta to embryos in the present study.…”
Section: Discussionmentioning
confidence: 80%
“…On the other hand, during the course of toxicological evaluation for MWCNT, we have revealed the teratogenicity of MWCNT given intraperitoneally or intratracheally to mice . And we are strongly interested in the possible teratogenicity of other fibrous materials, especially of asbestos, because the transplacental transfer of asbestos fibers into embryos were evident in humans and experimental animals (Cunningham and Pontefract, 1974;Haque et al, 1992Haque et al, and 2001 Teratogenicity of asbestos in mice . To the best of our knowledge, there are no data available so far in the literature to describe either the presence or absence of the teratogenicity of asbestos.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, oral administration of chrysotile asbestos to pregnant mice resulted in fibers detected in the lung and liver of pups by EDXA-EM (Haque et al, 2001). …”
Section: Reproductive and Developemental Effects Of Asbestosmentioning
confidence: 99%
“…“Unknown” exposures indicate the data came from occupational exposure matrices, including textiles, insulation, or cement workers. Sources: a Haque, 1992; 1996; 1998; Tsurikova, 1992. b Haque, 2001. c Schneider, 1977. d Saat, 1980; Dopp, 1997; Stevens, 1983. e Germani, 1999; Langseth, 2004; Magnani, 2008; Pira, 2005; Reid, 2009; Acheson, 1982; Newhouse, 1985; Wignall, 1982; Berry, 2000. f Millette, 1983. g Graham, 1967. h Attanoos, 2000. i Polissar, 1982.…”
Section: Reproductive and Developemental Effects Of Asbestosmentioning
confidence: 99%